2023
DOI: 10.1093/fampra/cmac151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate-related risks and extreme events on health outcomes and health utilization of primary care in rural and remote areas: a scoping review

Abstract: Background Rural populations are at risk of climate-related impacts due to ecological and geographical determinants, potentially leading to greater morbidity and health utilization. They are often highly dependent on primary care services. However, no rural- or primary care specific synthesis of these issues has ever been conducted. This review aimed to identify, characterize, and summarize existing research on the effects of climate-related events on utilization and health outcomes of primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…This would mean minor to moderate heat-related symptoms for remote residents will be evident only through the analysis of PHC data and not hospital, ED, or medical retrieval data. We also argue that current heat-related health impacts are underestimated as PHC data have yet to be adequately analysed across Australia [166]. Not all heat-related effects will require hospital admissions, emergency visits, or ambulance call-outs [167].…”
Section: Discussionmentioning
confidence: 97%
“…This would mean minor to moderate heat-related symptoms for remote residents will be evident only through the analysis of PHC data and not hospital, ED, or medical retrieval data. We also argue that current heat-related health impacts are underestimated as PHC data have yet to be adequately analysed across Australia [166]. Not all heat-related effects will require hospital admissions, emergency visits, or ambulance call-outs [167].…”
Section: Discussionmentioning
confidence: 97%
“…One scoping review about the impact of climate related events on rural population only found two articles related to heatrelated illness in Australia. 36 Another review explored the effect of heat events on prehospital and retrieval service utilisation in rural and remote areas and found only two articles. 37 For both articles in this review, there was a significant increase in ambulance call-outs following heatwaves, with evidence of dose-response relationship in which there was an increased effect size seen in highseverity events.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the effects of extreme heat for all rural Australian populations is also limited. One scoping review about the impact of climate related events on rural population only found two articles related to heat‐related illness in Australia 36 . Another review explored the effect of heat events on prehospital and retrieval service utilisation in rural and remote areas and found only two articles 37 .…”
Section: Discussionmentioning
confidence: 99%